PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN DENGAN INOVASI SEBAGAI VARIABEL MEDIASI - Muhammad Rofiq Sunarko, Natalia Hadiani, Djoko Kristianto & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study is to analyze of: 1) the effect of accountinginformation system quality on employee performance 2) the effect of accountinginformation system quality to innovation 3) the effect of innovation on employeeperformance 4) the effect of quality of accounting information system onemployeeperformance with innovation as mediation variable. This research is a survey onemployee of finance and administration CV The Group's New Hope in Surakartaamounts to 35 people and all of them are sampled by census technique. This type ofdata used qualitative and quantitative data. Data source uses primary data andsecondary data. Methods of data collection used questionnaires and literature study.Data analysis technique used path analysis. The results showed that the quality ofAccounting Information System has a positive and significant effect on employeeperformance. Quality Accounting Information System has a positive and significanteffect on innovation. Innovation has a positive and significant effect on employeeperformance. Quality Accounting Information System has a positive and significanteffect on employee performance with innovation as a mediation variable.Keywords: quality of Accounting Information System, innovation, employeeperformance